Identity Development in an International Transracial Adoptive Family: A 5-Year Case Study. Issue 4 (2nd October 2019) - Tan, Tony Xing; Liu, Yanhong
ABSTRACT: Our case study focused on the adoptive identity development of two female Chinese adoptees over the course of five years (from when they were 7 and 9 until they were 12 and 14 years old, respectively). The study investigated the adoptive parent's and family identities through six interviews with the adoptive mother, adoptees' behavioral adjustment reported by the mother, two unstructured observations, and exploration of adoptees' narratives. The study was guided by a narrative-based framework situated with the cultural socialization approach. Results highlight four central themes: 1) becoming Chinese-Americans ; 2) meaning related to adoption is both spoken and unspoken ; 3) a we-ness identity, and 4) social-cultural contexts of identity wor k. Findings demonstrate the incorporation of adoption and the adoptees' race and culture into the adoptive parent's and family identities. Findings further illuminate that one's identity is developed within personal, familial, and social-cultural contexts.